The Influence of Rupiah Exchange Rate, Bank Interest Rate, Inflation, and Profitability on Stock Prices: An Empirical Study on Companies Listed in the IDX30 Index on the Indonesia Stock Exchange - Apriyana, Gregorius Yudha Pratama; Hakim, Astrid Dita Meirina (Jurnal Multidisiplin Sahombu, 2025)
This study investigates the influence of the Rupiah exchange rate, bank interest rates, inflation, and profitability on stock prices, using companies listed in the IDX30 index on the Indonesia Stock Exchange as the empirical context. The variables examined represent key macroeconomic and firm-level indicators that are often considered by investors when evaluating equity investments. The study employs a quantitative approach through panel data regression to assess both individual and simultaneous effects. The findings reveal that the Rupiah exchange rate and profitability have a significant negative impact on stock prices, while inflation has a significant positive influence. Conversely, bank interest rates do not significantly affect stock prices. Simultaneously, the four variables jointly influence stock price fluctuations, indicating the complex dynamics between external economic factors and internal financial performance. These results offer insights for investors, regulators, and corporate decision-makers in understanding stock price behavior and enhancing investment strategies in dynamic financial markets.